Jestřáb na podivné stopě: Folklorní, mysteriózní a záhadologické motivy a inspirace v životě a díle Jaroslava Foglara - Jan Pohunek (Studia Ethnologica Pragensia, 2018)
Jaroslav Foglar (1907–1999, nicknamed „Jestřáb“ — „Hawk“) was a Czech scoutmaster and a prolific and influential author of novels, short stories, comics and practical guides for the youth. The article discusses motifs in his work and life that were influenced by contemporary folklore, Zeitungssagen, forteana and other similar genres. While Foglar was not an author of fantastic or supernatural prose and was strongly inclined to keep a skeptical stance in this manner, he was also able to successfully build an atmosphere of mystery in his literal works using aforementioned genres as an inspiration. Key topics discussed in the paper are roles and importance of staged hauntings in Foglar’s scout troop, appearance of various urban phantoms in his works and Foglar’s take on the story of disappearance of Charles Ashmore/Oliver Lerch/Olivier Thomas. These examples are further discussed in the context of scouts’ folklore, campfire legends and popular culture of the 20th century.